PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI FASE F SMA NEGERI 1 AMPEK ANGKEK - Sabilla, Aulia Safira (Jurnal Edukasi dan Penelitian Matematika, 2024)
The purpose of this study was to compare the performance of students taught using direct teaching with the Problem Based Learning (PBL) model. Quasy Experiment design based on posttest-only nonequivalent control group was used for this study. Students in the 2024-2025 academic year from Class X at SMA N 1 Ampek Angkek participated in this study. Taking the final test and quiz helped measure how well students could solve maths problems. Testing the null hypothesis (H0) resulted in a p-value = 0.002 at an actual significance level of 0.05. The improvement in ability compared to those who learnt directly was the result of using the PBL model..Keywords– Problem Solving Ability, Problem Based Learning Model, Direct Learning